2015
DOI: 10.1371/journal.pone.0136499
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Validation of Reference Genes in Infected Tomato Leaves for Quantitative RT-PCR Analyses

Abstract: The Gram-negative bacterium Xanthomonas campestris pv. vesicatoria (Xcv) causes bacterial spot disease of pepper and tomato by direct translocation of type III effector proteins into the plant cell cytosol. Once in the plant cell the effectors interfere with host cell processes and manipulate the plant transcriptome. Quantitative RT-PCR (qRT-PCR) is usually the method of choice to analyze transcriptional changes of selected plant genes. Reliable results depend, however, on measuring stably expressed reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 75 publications
4
42
0
Order By: Relevance
“…NormFinder enables grouping of the samples, and calculates the intra-and intergroup variation of candidate genes, and suggests suitable internal control gene. Our data indicated that all candidate genes displayed stability values below 1.5, suggesting for the housekeeping functions of the selected genes (Mascia et al, 2010;Lacerda et al, 2015;Müller et al, 2015) (Figure 2A, B). Meanwhile, the stability values output by geNorm and NormFinder analyses were distinctive for each candidate.…”
Section: Schemes To Select Stable Internal Control Gene Candidatesmentioning
confidence: 84%
See 1 more Smart Citation
“…NormFinder enables grouping of the samples, and calculates the intra-and intergroup variation of candidate genes, and suggests suitable internal control gene. Our data indicated that all candidate genes displayed stability values below 1.5, suggesting for the housekeeping functions of the selected genes (Mascia et al, 2010;Lacerda et al, 2015;Müller et al, 2015) (Figure 2A, B). Meanwhile, the stability values output by geNorm and NormFinder analyses were distinctive for each candidate.…”
Section: Schemes To Select Stable Internal Control Gene Candidatesmentioning
confidence: 84%
“…Then, two representative algorithms, geNorm and NormFinder, were applied (Andersen et al 2004; Vandesompele et al ). These algorithms are used to rate the constancy of expressions among samples (Lacerda et al 2015;Mascia et al 2010;Müller et al 2015). The geNorm analysis run by qBase+ software computes an expression stability values (M) for tested genes, as the average pairwise variation among candidates (Vandesompele et al 2002).…”
Section: Schemes To Select Stable Internal Control Gene Candidatesmentioning
confidence: 99%
“…For example, in Xanthomonas campestris pv. vesicatoria –tomato leaf infection experiments, the gene amplified by the IMP‐β primer set has previously been reported to be more stably expressed than those amplified by primer sets LSM7, COX and EF1‐α (Müller et al., ). This could not be confirmed herein where the IMP‐β primer set was outperformed by LSM7 primer set in terms of both expression stability and smaller variations when sample subsets were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…NormFinder uses a model‐based approach allowing intra‐ and inter‐group comparisons of the obtained Ct values, and it provides a ranking of the candidate reference genes based on the estimated standard deviations. Recent studies have proposed different reference genes for expression studies during tomato ( Solanum lycopersicum ) development (Expósito‐Rodríguez, Borges, Borges‐Pérez, & Pérez, ) and tomato–pathogen interactions (Fradin et al., ; Müller et al., ; Pombo et al., ). Primer pairs for ten of these genes—four classical housekeeping genes, such as elongation factor EF1‐ α and ATPase (Expósito‐Rodríguez et al., ; Pombo et al., ), and six newly suggested ones (Müller et al., ; Pombo et al., )—were selected and evaluated in tomato–grey mould interaction.…”
Section: Introductionmentioning
confidence: 99%
“…2011; Müller et al . 2015), and the gene expression levels are given as the relative numbers of copies.…”
Section: Methodsmentioning
confidence: 99%